Identifying Students’ Coping Strategies In Dealing With Academic Stress At Sintuwu Maroso University - Tarinje, Olviani Cipta Ningsi; Tarusu, Novriyanto (Universitas Sintuwu Maroso, 2025)
Abstract: The objective of this study is to find out students' coping strategies in dealing with academic stress at Sintuwu Maroso University Poso. This type of research uses a quantitative survey method through Google Forms. The subjects of this study is active students in 2024, the number of the students is 47. The data is collected by distributing questionnaire links to each English Teacher in English Study Program. The results of this study indicate that on the subscale Self Distraction, the subjects are used to doing other activities to switch their minds from the problem they have, such as watching TV, sleeping, reading, or shopping (82.71%). On the subscale Religion, most subjects (80,85%) often find comfort in their religion by praying or meditating. Of course, the subjects are Indonesian, so Indonesians highly uphold religious values. On the subscale Acceptance, the subjects already accept and try to live with reality (80,59%). For the Active Coping (77,93%), shows that the subjects take action and try to focus on their efforts and make the situation better. For the Positive reframing (75,53%), the subjects try positive thinking when facing the situation. For the Planning (74,47%), when dealing with a situation, the subjects think hard about what to do next and make a strategy to face the situation they are in. Using Instrumental Support (71,01%), the subjects seek help or advice from others to improve the situation. The 7 subscales explained above show that six subscales in the adaptive category were Religion, Acceptance, Active Coping, Positive Reframing, Planning, and Using Instrumental Support. Only one subscale, self-distraction, is in the maladaptive category.